Tinea pseudoimbricata por M. gypseum associada à escabiose crostosa Tinea pseudoimbricata caused by M. gypseum associated to crusted scabies - Claudia Schermann Poziomczyk; Bruna Köche; Fabio Luis Becker; Sérgio Ivan Torres Dornelles; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2010)
Tinea pseudoimbricata é relacionada ao T. tonsurans e ao T. rubrum e a escabiose crostosa é uma dermatose altamente contagiosa, ocasionada pela proliferação excessiva do S. scabiei var. hominis. Descrevemos uma paciente com 21 anos, soronegativa para HIV, apresentando ambas doenças dermatológicas. O encontro simultâneo destas dermatoses em pacientes imunocompetentes é muito raro. Tinea pseudoimbricata is related to T. tonsurans and T. rubrum and crusted scabies is a highly contagious dermatosis caused by excessive proliferation of S. scabiei var. hominis. We described a case of a 21-year-old patient, seronegative for HIV, with both skin diseases. The occurrence of these dermatosis simultaneously in immunocompetent patients is very rare.